2021
DOI: 10.1177/14613557211036721
|View full text |Cite
|
Sign up to set email alerts
|

The role of context in understanding the use of tactical officers: A brief research note

Abstract: A small body of research suggests that the use of police tactical officers has become normalized in that they now commonly respond to “routine” calls rather than being restricted to high-risk situations. However, this research has tended to rely on crude data (i.e., call type), which fails to account for the context of the calls (e.g., the presence of potential risk factors that might warrant tactical resources). In this brief research note, we sought to expand upon previous literature by examining the risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Second, the discussion of weapons in our interviews, as made clear in our paper, did not centre on common household items, such as 'baseball bats in closets', but on objects that were being brandished as weapons and the potential presence of firearms. A re-examination of some of the data released to Roziere and Walby (2018) confirmed the importance of weapons as a potential risk factor (Jenkins et al, 2021). For example, our reanalysis of tactical responses in Winnipeg that included additional contextual information (n ¼ 1019) 1 suggested that responding officers believed that weapons were on scene prior to responding in nearly 60% (n ¼ 610) of calls, and that the majority of these weapons (n ¼ 460, 75%) were believed to be firearms, such as rifles, handguns, and sawed-off shotguns.…”
Section: Misunderstandingsmentioning
confidence: 92%
“…Second, the discussion of weapons in our interviews, as made clear in our paper, did not centre on common household items, such as 'baseball bats in closets', but on objects that were being brandished as weapons and the potential presence of firearms. A re-examination of some of the data released to Roziere and Walby (2018) confirmed the importance of weapons as a potential risk factor (Jenkins et al, 2021). For example, our reanalysis of tactical responses in Winnipeg that included additional contextual information (n ¼ 1019) 1 suggested that responding officers believed that weapons were on scene prior to responding in nearly 60% (n ¼ 610) of calls, and that the majority of these weapons (n ¼ 460, 75%) were believed to be firearms, such as rifles, handguns, and sawed-off shotguns.…”
Section: Misunderstandingsmentioning
confidence: 92%
“…Differential enforcement in the case of black and white suspects in the United States has been observed in differential protective and arresting actions by the Police in case of black and white protesters (Gamal, 2016). Police militarization and special Police units used for simple processes like service of summons is a peculiar problem in the United States (Jenkins et al, 2021). Police militarization and the narrative of a 'hero cop' also exacerbates pan-racial police violence profiles (Steinberg, 2015).…”
Section: Differential Enforcement Community Control and Ecological Fa...mentioning
confidence: 99%